Analisis Sikap Mandiri Siswa SMAN 2 Kota Jambi - Muhammad Iqbal; Rizka Octavia Sandra (Cahaya Ilmu Cendekia Publisher, 2022)
Research objectives: This study aims to determine how the attitudes towards physics students at SMAN 2 Jambi City are seen from 3 indicators Methodology: The research method in this study uses quantitative methods, with a sample of 60 students. The main findings: The results of this study are an analysis of students' attitudes towards physics which will be seen from 3 indicators, namely indicators of fun learning physics, interest in increasing the time to study physics, and interest in a career in physics where from the results of research students are in the sufficient category so that students already have attitudes towards physics are sufficient and need to be continuously improved so that students will be able to have a positive attitude towards learning physics. The novelty of the research: The novelty of this research is in analyzing attitudes towards physics where the analysis of attitudes towards physics is based on 3 indicators.